Overcoming the Abuse of Sharp Weapons by Children: A Study at the Dompu Police Station - Rahmania, Nunung; Alqurayvin, Shandy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The misuse of sharp weapons by children is a social phenomenon that is rampant and troubling the community in Indonesia, especially in the jurisdiction of Dompu Police Station. The purpose of this research is to find out the countermeasures for the misuse of sharp weapons committed by children at Dompu Police Station. The type of research used is empirical research which examines the facts that occur in the field with thestatute approach andcase approach methods. The results of the study found that the form of overcoming the abuse of sharp weapons by children at Dompu Police Station through 2 (two) ways, namely preventive (prevention) and repressive (handling). The preventive measures taken by the Women and Children Protection Unit at Dompu District Police are online and offline socialization: online socialization through zoom with participants from all teacher representatives from all schools in Dompu District and offline socialization at schools, coordination with Babin Kamtibnas, and patrols during vulnerable times such as at night. Meanwhile, the handling of sharp weapon abuse by children in the Women and Children Protection Unit at Dompu Police Station is carried out based on Law Number 11 of 2012 concerning the Child Criminal Justice System and has been carried out properly.